The Role of Civic Education in Strengthening Political Literacy, Political Awareness, and Political Participation Among University Students: A Case Study at PGRI University Yogyakarta - Stanislaus Jebarus; Sunarso Sunarso (International Journal of Applied Research and Innovation, 2026)
This study examines the role of Citizenship Education in strengthening political literacy, political awareness, and political participation among students at Universitas PGRI Yogyakarta. Employing an empirical qualitative approach with a case study design, the research collected data through semi-structured interviews, participant observation, and document analysis involving Citizenship Education lecturers and undergraduate students who had completed the course. The findings indicate that Citizenship Education contributes significantly to the development of political literacy by enhancing students’ understanding of democratic institutions, constitutional principles, critical political analysis, and information verification skills in digital environments. The learning process also fosters political awareness through the internalization of civic values, reflective engagement with public issues, and the cultivation of democratic responsibility. Political participation is strengthened through increased involvement in student organizations, civic discussions, digital engagement, and community-oriented activities. Democratic classroom practices, contextual learning, and dialogical interactions emerged as important factors supporting civic competence development. The study demonstrates that Citizenship Education functions as a strategic mechanism for preparing politically literate, critically aware, and actively engaged citizens capable of contributing to democratic life in contemporary society.